AS-SB ENERGETICS IN ARGENTIAN SULFOSALTS - Ghosal S.; Sack R.O. (My University, 1995)
Experimental brackets on As-Sb partitioning between polybasite-pearceite {Pbp; (Cu, Ag)16(Sb, As)2S11} and pyrargyrite-proustite {Ppr; (Cu, Ag)3(Sb, As)S3}, and between pyrargyrite-proustite, and miargyrite and smithite {αMi, βMi, Smt; Ag(Sb, As)S2} (350-400°C; evacuated silica tubes) define standard state Gibbs energies of the As-Sb exchange reactions {Ag16As2S11 + Ag3SbS3 = Ag16Sb2S11 + Ag3AsS3, ΔG° Pbp-Pprr = 0.65 +/- 0.60 kJ/gfw; Ag3AsS3 + AgSbS2 = Ag3SbS3 + AgAsS2, ΔG° Ppr-αMir = 3.10 +/- 0.50 kJ/gfw, ΔG° Ppr-Smtr = 1.70 +/- 0.50 kJ/gfw} and the nonidealities associated with the As-Sb substitutions in these minerals (measured by symmetric regular-solution parameters for formula units on a one As-Sb site basis; WPbpAsSb = 4.00 +/- 0.25 kJ/gfw; WPprAsSb = 6.00 +/- 0.60 kJ/gfw; WαMiAsSb = WSmtAsSb = 7.00 +/- 0.50 kJ/gfw). The above constraints applied to the miscibility gap between Ag(Sb, As)S2 solutions with α-miargyrite and smithite structures at 350°C determine the relative stabilities of these structures in the As and Sb endmembers to be: (G°,αMiSb -G°,SmtSb ) # -0.63 kJ/gfw; (G°,αMiAs -G°,SmtAs ) # 0.77 kJ/gfw. Combining these constraints with the calorimetric data of Bryndzia and Kleppa (1988, 1989) and our melting point determinations we have constructed a phase diagram for the AgSbS2 - AgAsS2 subsystem. The salient features of this diagram are (1) eutectic behaviour (T # 396°C, XAs # 0.50), (2) modest increase in the temperature of the α -> β miargyrite transition with As substitution (#380°C in Sb-subsystem; #386.6°C at XMiAs # 0.36), (3) a 42.5°C depression of the trechmannite-smithite transition with preferential incorporation of Sb in smithite {smithite (XAs # 0.62) -> α-miargyrite (XAs # 0.34) + trechmannite (XAs # 1.00) at #277.5°C}, and (4) widening of the miargyrite-trechmannite gap at lower temperatures. The latter feature is consistent with the inference that the most As-enriched epithermal miargyrites crystallized at temperatures above 195°C.